Luminescent Supramolecular Heterometallic Macrocycles and their Encapsulation on Cholate Gels. Issue 41 (25th October 2018) - Gavara, Raquel; Mateos, Javier; Sabaté, Ferran; Belda, Raquel; Llinares, José Miguel; García‐España, Enrique; Rodríguez, Laura
Abstract : The metal complex formed by coordination of Zn II to 1, 7‐bis(4‐methylpyridine)‐4‐(2‐naphthylmethyl)‐1, 4, 7‐triazaheptane (ZnL 2+ ) was reacted in aqueous solution with [Pd(NO3 )2 (en)] and [Pt(NO3 )2 (en)] salts to form the self‐assembled heterometallic macrocycles[Zn2 L2 Pd2 (en)2 ] 8+ and[Zn2 L2 Pt2 (en)2 ] 8+, respectively. Pd II and Pt II ‐coordination modulates the original emission ofZnL 2+ arising from the presence of the naphthalene chromophore and the formation of the macrocycles can be monitored due to the PET process occurring with coordination of Pd II and Pt II to the pyridine units ofZnL 2+ . Additionally, several studies reveal that these heteromacrocycles can be encapsulated in Zn II ‐cholate hydrogels giving rise to soft materials with tunable emissive properties. Preliminary analysis show also that the addition of the metallic species in micromole concentration to the cholate hydrogels resulted in an improved mechanical strength of the final materials. Abstract : The Zn II complex of 1, 7‐bis(4‐methylpyridine)‐4‐(2‐naphthylmethyl)‐1, 4, 7‐triazaheptane is able to interact with Pd II and Pt II salts to form heterometallomacrocycles. The encapsulation of these species at micromolar concentration into cholate hydrogels, gives rise to materials with emissive and improved mechanical properties.